Hemiplegic shoulder pain, a combined approach with suprascapular nerve block and intra-articular corticosteroid injections: a case series - Gahier, Matthieu; Lecler, Andy; Gadbled, Guillaume; Arnolfo, Paul; Gross, Raphael (Frontiers in Neurology, 2025)
BackgroundHemiplegic shoulder pain (HSP) is a prevalent and disabling condition affecting patients after stroke or traumatic brain injury. There is currently no consensus regarding infiltrative strategies. A combined approach, involving suprascapular nerve block and intra-articular corticosteroid injection, has been proposed for HSP and capsulitis, yet evidence remains limited.ObjectiveThis study presents the results (efficacy and safety) of this combined approach to alleviate pain and improve passive range of motion (PROM).MethodsA retrospective, multicenter observational study (36 patients).ResultsAt 1 month, the mean pain intensity (visual analogue scale VAS) significantly decreased from 6.5 ± 1.5 at baseline to 1.9 ± 2.1, and PROM showed significant improvement across all three planes (mean PROM gains: 28.4° in abduction, 29.2° in flexion, and 13.4° in external rotation). The benefits were largely maintained at 3 months, and no serious complications were observed (one vasovagal episode).ConclusionThe combined approach is a clinically feasible, safe, and effective method for treating HSP in PRM settings.